Resource-related inequalities in mothers' employment in two family-policy regimes: evidence from Switzerland and West Germany. Issue 1 (1st January 2017) - Liechti, Lena
ABSTRACT: Using data from the Swiss Household Panel (1999–2012) and the German Socio-Economic Panel (1994–2010), this paper compares the impact of mothers' education and her partners' income on maternal employment within the second to the fourth year after childbirth in Switzerland and West Germany. The broadly similar institutional context in the two countries makes for a more controlled and narrower comparison. Around the turn of the millennium, both family-policy regimes did little to foster dual-earner families. However, they differed in their support for families' caring role (familialistic policies), with West Germany being much more generous. It is expected that these familialistic policies widen the educational gap in maternal employment, by selectively encouraging less-educated mothers to stay at home. Moreover, they are also expected to lower the economic pressure on low-income families to have a second income, thus diminishing the impact of partners' income. Results confirm this expectation only within the fourth year after childbirth but not within the years before. This is somehow surprising, as central country-differences with respect to familialistic policies refer to the first three years after childbirth.